Politik Hukum di Era Pemilu yang Jujur dan Adil - Heriyanto Heriyanto (Pusat Riset dan Inovasi Nasional, 2025)
Law constitutes a set of rules that must be obeyed and implemented by every individual. The concept of law-making forms part of the broader meaning of legal politics, serving as a guideline for the governance of the state and the life of society. Law is a necessity for all components of the nation and the state to create security and order, thereby providing a sense of justice. General elections (Pemilu) conducted directly by the people, from the people, and for the people serve as a means of manifesting sovereignty for the state to produce a democratic government based on Pancasila and the 1945 Constitution. The administration of general elections direct, free, universal, and secret must be carried out honestly and fairly, capable of realizing national integration, professionalism, and accountability in order to position the people as the primary holder of sovereignty. This study employs a normative juridical legal research method with a statutory approach and a conceptual approach. The results of this research indicate that the legal concept concerning general elections depends on legal politics, which acts as a determining activity in the pattern and formation of election legislation designed to oversee and renew that law as a determination of politics related to democracy in the country. This study aims to ascertain the impact of the implementation of legal politics in the post-reform general election system and represents an existence of legal politics within Indonesia’s legal enforcement system.